Is the ETS an effective environmental policy? Undesired interaction between energy-mix, fuel-switch and electricity prices - Bersani, Alberto M.; Falbo, Paolo; Mastroeni, Loretta (Energy economics, 2022)
We consider the optimal energy-mix decision for the electricity sector subject to an emission trading system (ETS) under uncertain demand. Under the assumption that power producers maximize the expected profit of their sector, we show that an ETS introduces weird effects to the emission reduction target. On one hand, in terms of generation merit order, it certainly favors fuel switching between coal and gas plants. However, in the long run, the ETS hinders the expansion of renewable technology capacity, rather than promoting it. Moreover, expected emissions increase with respect to a business-as-usual scenario. Moreover, our analysis shows that under certain conditions, not unusual in real life, the equilibrium price of emission certificates is not just the expectation of a payoff for a binary option. A third value is possible. It coincides with the price that makes generation by coal- or gas-fired plants indifferent. •We consider the optimal energy-mix decision for the electricity sector subject to an ETS under uncertain demand.•We show that an ETS introduces weird effects to the emission reduction target.•We show that in the long run, the ETS hinders the expansion of renewable technology capacity, rather than promoting it.•We show that under certain conditions the equilibrium price of emission certificates is not just the expectation of a payoff for a binary option.